A graphene/carbon nanotube@π-conjugated polymer nanocomposite for high-performance organic supercapacitor electrodes1. Issue 7 (21st February 2015) - Sun, Minqiang; Wang, Gengchao; Yang, Chongyang; Jiang, Hao; Li, Chunzhong
<x xml:space="preserve">Abstract</x> An intriguing organic supercapacitor based on hierarchical porous GNS/aMWCNT@poly(1, 5-diaminoanthraquinone) is fabricated with superhigh energy density and excellent cycling stability.